Mobilisasi Islamis Damai di Dunia Muslim: Peran Partisipasi Politik dan Kapasitas Negara - Testriono, Testriono (Studia Islamika, 2010)
Book Review : Julie Chernov Hwang,Â Peaceful Islamist Mobilization in the Muslim World: What Went Right (New York: Palgrave Macmillan, 2009), xviii + 212This book seeks to explain the variations within the Islamist mobilizations, which can be classified into: first, peaceful mobilization, which includes the creation of political parties, election, cooperation, creating civic alliance, and building civil movements. Second category is violent Islamist mobilizations articulated in the form of rebellion, riot, collective violence, and attacks on individuals and groups, minority groups, and private property.DOI:Â 10.15408/sdi.v17i2.465